2012
DOI: 10.1029/2011jc007787
|View full text |Cite
|
Sign up to set email alerts
|

Modeling waves and wind stress

Abstract: [1] A model for wave and wind stress prediction is constructed. The source functions that drive the space-time evolution of the energy spectra are developed in form based on theory and laboratory and field experiments. The calibration factors (proportionality constants of the source functions) are determined from a comparison of modeled and observed significant height and mean period. The observations are for the month of January 2005 and are derived from an array of laser range finders mounted on a bridge bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
130
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 36 publications
2
130
0
2
Order By: Relevance
“…Figure 12 Slopes, winds, and wave heights. Here we plot output from the Donelan et al [32] wave model using the Titan parameters from Hayes et al [12]. As the solid line we plot the expected RMS surface slope (our σ ) is as a function of the wind speed as measured 10 meters above the surface (U 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 12 Slopes, winds, and wave heights. Here we plot output from the Donelan et al [32] wave model using the Titan parameters from Hayes et al [12]. As the solid line we plot the expected RMS surface slope (our σ ) is as a function of the wind speed as measured 10 meters above the surface (U 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…We use the equations and parameters from Hayes et al [12] and derive an explicit wavefield using the model of Donelan et al [32], adapted to include surface tension effects (i.e., capillary-gravity waves and capillary waves). From these we calculate the expected value for both the wave angle σ and the significant wave height (defined as 4 times the http://www.planetary-science.com/content/3/1/3 root mean square (RMS) surface height) under Titan conditions ( Figure 12) and assuming that the liquid viscosity is that of pure methane.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous modeling studies have investigated how the wind stress and drag coefficient are modified by different sea states, including growing seas (e.g., Makin and Kudryavtsev 2002;Moon et al 2004b;Kukulka and Hara 2008;Mueller and Veron 2009) and complex seas (e.g., Moon et al 2004a;Donelan et al 2012;Reichl et al 2014). They all start with the momentum conservation constraint that the wind stress is equal to a sum of the momentum flux into surfaces waves (form drag of surface waves) and the momentum flux directly into the subsurface currents through viscous stress.…”
Section: Introductionmentioning
confidence: 99%
“…This step is needed to establish a relationship between the wind stress and the wind speed (normally at 10-m height). The wind profile in some studies is simply approximated using log-layer vertical wind profiles (e.g., Kudryavtsev and Makin 2001;Mueller and Veron 2009;Donelan et al 2012). In this case, the wind profile is dependent only on the surface roughness parameter z 0 , that is, the feedback appears only in the parameterization of the sea state-dependent z 0 .…”
Section: Introductionmentioning
confidence: 99%
“…The slope of the high-frequency end of the wave spectrum becomes steeper when the wave nonlinearity increases. Donelan et al (2012) found that in addition to the k −4 dissipation, swells modulate the equilibrium in breaking waves dependent on the mean surface slope, while Melville (1994) also quantified a relation between wave packet slopes and the dissipation rate. These results are specific to breaking waves, but one might expect similar relations between surface dynamics and dissipation rates for non-breaking waves.…”
Section: Wave Spectrummentioning
confidence: 99%